JENAYAH ROGOL DI DALAM UNDANG-UNDANG ISLAM - Nik Wajis, Nik Rahim (Jurnal Syariah, 2019)
Fuqaha in the past normally did not distinguish between adultery and rape as for the two terms share many similarities. However, they considered rape as a forced adultery. The article separate the two acts in terms of their characteristics and the type of evidence needed for rape case and form of sentences to be imposed on the rapist.